Cardiopulmonary exercise testing for identification of patients with hyperventilation syndrome - Brat, Kristian; Stastna, Nela; Merta, Zdenek; Olson, Lyle J.; Johnson, Bruce D.; Cundrle, Ivan (PloS one, 2019)
Measurement of ventilatory efficiency, defined as minute ventilation per unit carbon dioxide production (VE/VCO2), by cardiopulmonary exercise testing (CPET) has been proposed as a screen for hyperventilation syndrome (HVS). However, increased VE/VCO2 may be associated with other disorders which need to be distinguished from HVS. A more specific marker of HVS by CPET would be clinically useful. We hypothesized ventilatory control during exercise is abnormal in patients with HVS. Patients who underwent CPET from years 2015 through 2017 were retrospectively identified and formed the study group. HVS was defined as dyspnea with respiratory alkalosis (pH >7.45) at peak exercise with absence of acute or chronic respiratory, heart or psychiatric disease. Healthy patients were selected as controls. For comparison the Student t-test or Mann-Whitney U test were used. Data are summarized as mean ± SD or median (IQR); p<0.05 was considered significant. Twenty-nine patients with HVS were identified and 29 control subjects were selected. At rest, end-tidal carbon dioxide (PETCO2) was 27 mmHg (25-30) for HVS patients vs. 30 mmHg (28-32); in controls (p = 0.05). At peak exercise PETCO2 was also significantly lower (27 ± 4 mmHg vs. 35 ± 4 mmHg; p<0.01) and VE/VCO2 higher ((38 (35-43) vs. 31 (27-34); p<0.01)) in patients with HVS. In contrast to controls, there were minimal changes of PETCO2 (0.50 ± 5.26 mmHg vs. 6.2 ± 4.6 mmHg; p<0.01) and VE/VCO2 ((0.17 (-4.24-6.02) vs. -6.6 (-11.4-(-2.8)); p<0.01)) during exercise in patients with HVS. The absence of VE/VCO2 and PETCO2 change during exercise was specific for HVS (83% and 93%, respectively). Absence of VE/VCO2 and PETCO2 change during exercise may identify patients with HVS.